Professional values of undergraduate nursing students: A cross-sectional study - Cosmai, Simone (Nursing ethics, 2026)
Background: Professional values form the ethical foundation of nursing practice and are essential for developing moral reasoning and integrity in care delivery. The internalization of these values begins during undergraduate education through academic coursework, clinical experiences, and role models. Understanding how Italian nursing students perceive and prioritize professional values is crucial for curriculum development and preparing future nurses for ethically demanding clinical environments.Objective: To investigate the importance that undergraduate nursing students assign to professional values using the Italian version of the Nursing Professional Values Scale-3 (I-NPVS-3).Methods: A cross-sectional multicenter study was conducted between March and July 2024 among 463 nursing students enrolled in Bachelor programs across four Italian universities. The 28-item I-NPVS-3 scale assessed three domains: Caring, Activism, and Professionalism. Participants rated each item's perceived importance on a 5-point Likert scale. Data were collected using Microsoft Forms and analyzed using descriptive statistics, Welch's t-tests, and ANOVA.Results: Of 463 students, 358 completed surveys were analyzed (77% response rate). The sample comprised 45% first-year students, with 77% female participants and mean age of 23 years. Students assigned high average scores to professional values overall (mean 4.5, SD 0.74). The Caring domain received the highest mean score (4.67, SD 0.55), followed by Activism (4.32, SD 0.63) and Professionalism (4.21, SD 0.71). ?Respecting the inherent dignity, values, and human rights of all individuals? was the most valued item (82% rating it as extremely important). Female students scored higher across all domains compared to males. Younger students emphasized Caring more, while older students showed greater interest in Activism and Professionalism, though differences were not statistically significant.Conclusions: Italian nursing students prioritize Caring values most highly, emphasizing dignity, respect, and patient-centered care. The findings suggest curriculum enhancements should focus on strengthening Activism and Professionalism domains, particularly research engagement and policy involvement, to better prepare future nurses for evolving healthcare challenges.